The Rise of Duterte A Populist Revolt against Elite Democracy - Heydarian, Richard Javad (Springer Singapore, 2018)
This book draws on the extensive literature on populism, democracy, and emerging markets as well as interviews with senior government officials, experts, and journalists in the Philippines and beyond, This book is the first to analyze the significance and implications of the rise of Filipino president Rodrigo Duterte within a rapidly-changing Asia Pacific region. As China's power in the Pacific grows rapidly, nations that have traditionally been US allies, such as the Phillipines, are experiencing political convulsions; Duterte's open willingness to realign towards China (at the expense of America) in exchange for infrastructure investment is one of the clearest indicators of what China's rise might look like for nations around the world. Timely, precise, accessible and fast-paced, this book will be of value to scholars, journalists, policy-makers, and China watchers. .